Ferrihydrite decreases arsenic and cadmium bioaccessibility in microplastic-contaminated soils: Roles of iron speciation and surface charge transformation - Zelin Xu; Nan Yang; Peng Xiao; Qi Luo; Jingnan Ma; Wen Tian; Xiyan Jiang; Hanjun Zhu; Damao Xu; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Environmental Chemical Engineering, 2026)

Polyamide microplastics outperform polylactic acid in reducing cadmium health risks in arsenic-cadmium co-contaminated water: Insights from experimental and theoretical analysis - Zelin Xu; Xiyan Jiang; Jingnan Ma; Pengfei Wang; Peng Xiao; Nan Yang; Damao Xu; Shibo Yan; Hanjun Zhu; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2026)

Unraveling the critical role of nanoplastics in governing the interfacial behavior and toxicity evolution of ciprofloxacin during Fenton oxidation process - Hanjun Zhu; Haishuai Cui; Guopei Huang; Hai Yang; Jukun Xiong; Meimei Ran; Xiaoping Lin; Quan Wan; Lele Yang; Zelin Xu; Xin Nie (Chemical Engineering Journal, 2026)

The role of liver sinusoidal endothelial cells in metabolic dysfunction-associated steatotic liver diseases and liver cancer: mechanisms and potential therapies - Hanjun Mo; Pengfei Yue; Qiaoqi Li; Yinxi Tan; Xinran Yan; Xinyue Liu; Yuanwei Xu; Yingzhe Luo; Suruiya Palihati; Cheng Yi; Hua Zhang; Minlan Yuan; et al. (Angiogenesis, 2025)

The Impact of Bilateral Cerebellar Transcranial Direct Current Stimulation on Balance Control in Healthy Young Adults - Xin Huang; Zhiqin Xu; Lingxiang Zhou; Ke Dong; Qingqing Liu; Jiating Li; Di Lei; Hanjun Liu; Xi Chen (The Cerebellum, 2024)

Full-spectrum-responsive Ti4O7-PVA nanocomposite hydrogel with ultrahigh evaporation rate for efficient solar steam generation - Xinye Xu; Qi Zhao; Qi Liu; Junxiao Qiu; Jinhao Li; Wenqian Zheng; Jie Cao; Lina Wang; Wen Wang; Shutong Yuan; Anni Fu; Hanjun Yang; et al. (Desalination, 2024)

PKHD1L1, a gene involved in the stereocilia coat, causes autosomal recessive nonsyndromic hearing loss - Shelby E. Redfield; Pedro De-la-Torre; Mina Zamani; Hanjun Wang; Hina Khan; Tyler Morris; Gholamreza Shariati; Majid Karimi; Margaret A. Kenna; Go Hun Seo; Hongen Xu; Wei Lu; et al. (Human Genetics, 2024)
Identification of genes associated with nonsyndromic hearing loss is a crucial endeavor given the substantial number of individuals who remain without a diagnosis after even the most advanced genetic testing. PKHD1L1 was established as necessary for the formation of the cochlear hair-cell stereociliary coat and causes hearing loss in mice and zebrafish when mutated. We sought to determine if biallelic variants in PKHD1L1 also cause hearing loss in humans. Exome sequencing was performed on DNA of four families segregating autosomal recessive nonsyndromic sensorineural hearing loss. Compound heterozygous p.[(Gly129Ser)];p.[(Gly1314Val)] and p.[(Gly605Arg)];p[(Leu2818TyrfsTer5)], homozygous missense p.(His2479Gln) and nonsense p.(Arg3381Ter) variants were identified in PKHD1L1 that were predicted to be damaging using in silico pathogenicity prediction methods. In vitro functional analysis of two missense variants was performed using purified recombinant PKHD1L1 protein fragments. We then evaluated protein thermodynamic stability with and without the missense variants found in one of the families and performed a minigene splicing assay for another variant. In silico molecular modeling using AlphaFold2 and protein sequence alignment analysis were carried out to further explore potential variant effects on structure. In vitro functional assessment indicated that both engineered PKHD1L1 p.(Gly129Ser) and p.(Gly1314Val) mutant constructs significantly reduced the folding and structural stabilities of the expressed protein fragments, providing further evidence to support pathogenicity of these variants. Minigene assay of the c.1813G>A p.(Gly605Arg) variant, located at the boundary of exon 17, revealed exon skipping leading to an in-frame deletion of 48 amino acids. In silico molecular modeling exposed key structural features that might suggest PKHD1L1 protein destabilization. Multiple lines of evidence collectively associate PKHD1L1 with nonsyndromic mild–moderate to severe sensorineural hearing loss. PKHD1L1 testing in individuals with mild–moderate hearing loss may identify further affected families.

In-doping induced resonant level and thermoelectric performance enhancement in n-type GeBi2Te4 single crystals with intrinsically low lattice thermal conductivity - Peng Chen; Bin Zhang; Hanjun Zou; Xiangnan Gong; Yanci Yan; Jingwei Li; Daliang Zhang; Guang Han; Xu Lu; Hong Wu; Yun Zhou; Xiaoyuan Zhou; et al. (Chemical Engineering Journal, 2023)

Effective adsorption of ammonium nitrogen by sulfonic-humic acid char and assessment of its recovery for application as nitrogen fertilizer - Qianqian Sun; Hanjun Zhou; Chenyang Xu; Yu Ba; Zengchao Geng; Diao She (Science of The Total Environment, 2023)

iTRAQ-based proteomic analysis reveals the underlying mechanism of postmortem tenderization of refrigerated porcine Longissimus thoracis et lumborum muscle - Long Xu; Yueshan He; Xiaoyu Yuan; Kelin Liu; Yue Cui; Hanjun Ma; Changming Ma; Xiaoling Yu (Meat Science, 2023)

Study on engineering application method of large-scale reaction mechanism in knock prediction - Hanjun Xu; Jian Wu; Jingsi Wei; Ceyuan Chen; Mingjia Liu; Shan Wu (Fuel, 2023)

Expressional profiling study revealed unique expressional patterns and dramatic expressional divergence of maize α-zein super gene family - Lingna Feng; Jia Zhu; Gang Wang; Yuanping Tang; Hanjun Chen; Weibo Jin; Fei Wang; Bing Mei; Zhengkai Xu; Rentao Song (Plant Molecular Biology, 2009)